(3eWdY GdHOhQ heLeY GdHMhQs - (3CMeO Hf UGdM Hf CHj GdQLGd Gdjefj, Uaj GdOjf ,GHf nCHj GdpqQnLGd,J (B1092 (3g` s
(3ChdgG (B:s
(3jHJOF GdLRA HMQa GdZjf GdeYLeI HJQLeI ZGdH Hf YKeGf GdgeOGfi GdeTYGQi GdfGYWi ef Yjhf GdTjYI hCSjGOge s
(3BNQgG (B:s
(3hcGf jbhd HEeGeI GdHhSi jhSa GdfYeGf fe eYGUQi GdEeGe UdGM Hf Ydi Ydjg GdSdGe GfJgi hGdMeO ddg Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B137 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B253s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B535 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B561 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B184 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B4322/4) s
Keywords: (3GdJGQjNs